Construction and Validation of an Epigenetic Regulator Signature as A Novel Biomarker For Prognosis, Immunotherapy, And Chemotherapy In Hepatocellular Carcinoma - Cai, Jialiang; Wu, Suiyi; Zhang, Feng; Dai, Zhi (Frontiers in Immunology, 2022)
Epigenetic modification regulates various aspects of cancer biology, from tumor growth and invasion to immune microenvironment modulation. Whether epigenetic regulators (EGR) can decide tumor malignant degree and risk of immune evasion in liver hepatocellular carcinoma (LIHC) remains unclear. An epigenetic regulators signature called “EGRscore” was constructed based on bulk RNA-seq data of EGR in hepatocellular carcinoma (HCC). The correlation between EGRscore and overall survival (OS) was validated in HCC cohorts and other tumor cohorts. Mutation profiles, copy number alterations (CNAs), enriched pathways and response to immunotherapy and chemotherapy were compared between EGRscore-high and EGRscore-low patients. We found that EGRscore was associated with OS in HCC as well as several tumors including Glioma, Uveal Melanoma (UVM), Kidney tumors. Mechanism study demonstrated that distinct mutation profile of TP53 was present in EGRscore-high and EGRscore-low patients. Meanwhile, EGRscore-low patients were characterized with immune cells which promoting killing tumors. Furthermore, EGRscore was associated with genes regulating chemoresistance in HCC. Finally, we indicated that EGRscore-low patients had higher response rates to immunotherapy and chemotherapy. EGRscore could be used to distinguish overall survival, tumor progression, mutation pattern, and immune microenvironment. The present study contributes to improving hepatocellular carcinoma patient prognosis and predicting response to immunotherapy.